Simulation of CO2 Corrosion of Carbon Steel in High Pressure and High Temperature Environment (HPHT) - Yuli Panca Asmara (Asosiasi Staf Akademik Perguruan Tinggi Seluruh Indonesia (ASASI), 2022)
In HPHT environments, the mechanism of CO2 corrosion faces a challenge as an effect of chemical-physical reactions on the metal surface. The presence of other elements in the CO2 system complicates corrosion behavior. To provide a realistic mechanism for corrosion process, some corrosion prediction models have developed software using fundamental theories such as electrochemical reactions and thermodynamics theories. Existing methods to predict corrosion rate models in HPHT environments have shown reasonable results. This paper reviews software of corrosion predictions which calculate corrosion rate based on mechanistic theories that study effects of H2S, acetic acid (HAc) concentrations, shear stress, pH in temperature from 25oC – 100oC and pressure from 1–10 bar. From the simulation, corrosion rate increased significantly in the high pressure CO2 environment. Corrosion rate at pH 4 increased to 30 mm/y at a temperature from 15oC to 90oC. While at pH 8 corrosion rate reached 4 mm/y. This lower corrosion rate indicated a tendency for deposits formation at higher pH. Corrosion rate behaves in a different mechanism at high temperatures. The corrosion rate decreased to 4 mm/y when the temperature increased to more than 90oC. Effects H2S gas and HAc were identified to increase corrosion rate. Both elements provide extra cathodic reaction and create limiting current density in the cathodic reaction process based on polarization sweep models. However, the polarization graph calculated using corrosion models could not display passive behavior in the anodic polarization process. Thus, further, improvement should be considered. From the data calculation, it can be shown that corrosion prediction software can predict corrosion rate in HPHT conditions.